Demonstration of Mass Transfer Using Aeration of Water - Syeda, Sultana R; Arifin, BMS; Islam, Md M; Kumar, Anup (Journal of Chemical Engineering, 2011)
An experiment was developed using aeration of water for demonstrating the phenomenon of mass transfer. The demonstration was designed to provide both conceptual and practical insight of the mass transfer process. A bubble column fitted with a sieve tray was used to carry out the experiment. The air flow rate and hole size of the sieve tray were varied. Mass transfer coefficient was obtained from the initial and final oxygen concentrations of the aerated water. A dimensionless correlation for mass transfer coefficient in terms of the experimental variables was developed by dimensional analysis and regression of the experimental data. The demonstration is suitable for chemical and other engineering students and can be fit in one laboratory session of three hours. The experimental setup is simple and inexpensive, and can be developed in-house. In addition to the laboratory demonstration, the experiment can also be used for optimizing design parameters of industrial aeration tanks. Keywords mass transfer coefficient; aeration; bubble column; dimensional analysis; Stanton number. DOI: 10.3329/jce.v25i0.7239 Journal of Chemical Engineering, IEB Vol. ChE. 25, No. 1, December 2010 pp.56-60